Flavonoid Level Determination in Jamu Pegel Linu in Magelang Regency Using Uv-Visible Spectrophotometry - Selma Septi Pratiwi; Perdana Priya Haresmita; Missya Putri Kurnia Pradani; Arief Kusuma Wardani (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2023)
Jamu is made from the toga plant, which is still used medicinally in Indonesia. Rutin, a type of flavonoid component, is frequently present in herbal medicine pegel linu. Rutin serves as an antioxidant and anti-inflammatory by neutralizing free radicals, which helps to prevent tissue damage and relieve soreness. This research's objective was to evaluate the amounts of flavonoids in samples using UV-Visible spectrophotometry, employing three samples of herbal medicine (A, B and C) as well as the standard solution, reagents AlCl3 and sodium acetate. In this investigation, the protocol utilized to determine the maximum wavelength was 400–800 nm, and the result was 413.5 nm. The linear regression equation is y = 0.0471x + 0.0624 with a correlation coefficient of R2 of 0.9934 and a LOD value of 3.9694 mg / L and a LOQ value of 13.231 mg / L. The determination of total flavonoid levels considered as rutin uses concentrations of 10, 12.14, 16 and 18 ppm with operating time of 30 minutes. The findings of rutin content analysis for samples A, B, and C were 1.6683%, 2.8763%, and 3.0923%, respectively.